(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
In the mentioned article of the author, the problem of play in the experience of philosophical theory is considered, besides, as mentioned in it, play is much bigger than man. In its original form, it was formed in the universe of beings capable of moving in space. The game was necessary for young animals as a means of strengthening the body, mastering the methods of struggle for life, leaning on the experience of existence accumulated in the endless exchange of previous generations, and enjoying it. Here the activity is instinctive. A completely different method of activity appears in human society - activity based on a conscious goal. Purposiveness, which naturally arises in the processes of physical survival, beginning with finding food, gradually spreads to more complex spheres of human activity. In it, the initial uncertain gaming impulses are subdued.